2008
DOI: 10.1186/1476-7120-6-52
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of carotid plaque and intima-media thickness assessment in routine clinical practice

Abstract: Objectives: To describe the findings and evaluate appropriateness of a carotid artery study including the measurement of IMT, the presence of atherosclerotic plaque, and their correlation with cardiovascular risk factors.Methods: 555 patients (220 men; 67.06 ± 12.44 years) were included in the study. 120 patients (21.62%) presented carotid plaque: 108 (19.45%) in patients with at least one risk factor and 12 (2.1%) in patients without risk factors. With respect to appropriateness of the present studies: 65% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Th e mean CCA IMT increased with confi rm this hypothesis 21,31 . As was determined in the present study, the literature comprises the studies that reveal positive correlation between male gender and carotid IMT 7,10,11 . However, there are studies suggesting that gender has no eff ect on carotid IMT.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Th e mean CCA IMT increased with confi rm this hypothesis 21,31 . As was determined in the present study, the literature comprises the studies that reveal positive correlation between male gender and carotid IMT 7,10,11 . However, there are studies suggesting that gender has no eff ect on carotid IMT.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to the researchers in the literature stating that DM increases carotid IMT, there are also researchers reporting no relation 7,15,16,39,40 . In the present study, univariate analyses demonstrated that DM is among the risk factors eff ective on carotid IMT; whereas, regression analysis revealed no signifi cant eff ect of DM on carotid IMT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations